Privatizing Public Employment Assistance and Precarious Employment in Toronto - De Wolff, Alice (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[C]onsiders the effects of contracting-out of public employment services for employment place workers, on the one hand, and, on the other, the workers seeking employment whom they serve. In so doing, [the author] reveals a range of important connections, from linkages at the policy level between changing immigration policy and the provision of employment supports at the provincial level, to connections, by way of a common attachment to precarious employment, between community workers, working largely in serial fixed-term temporary contracts contingent on public funding, and their clients. --From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment